Instrumento para documentação da assistência de enfermagem à mulher no puerpério imediato - Silva, Aline Franco da (2012)
The systematization of nursing care for postpartum women is a way of organizing care and reduce the occurrence of complications during hospitalization. To this end, the nurse must apply the scientific knowledge of nursing and other sciences in the organization and structuring of such assistance, using as a tool the nursing process. Thus will ensure individual assistance, qualified and targeted to the real needs of postpartum. And, through the documentation of this process will give visibility to their actions, characterizing their professional practice in puerperal attention. The area lacks Obstetrical Nursing studies directed to research and development of tools that encourage the registration of the essential elements of the care process. Understanding the documentation of nursing care as an essential part of the care process, it is essential to develop research that contributes to fill this gap. This study aims to contribute for the documentation of professional practice puerperium from the elaboration of an instrument incorporating the following tools: the nursing process embodied in Theoretical Model of Basic Human Needs, the concept of the International Nursing Minimum Data Set, and the standardized language International Classification for Nursing Practice. Objective: To develop an instrument for documentation of nursing care to women immediately postpartum. Method: A structured methodology in three consecutive phases and interdependent. In the first phase, we performed a selection of identification data and empirical indicators to compose the first two parts of the instrument. The second phase was conducted to validate the contents of the first version of the instrument, using the Delphi technique. It is a technique of consensus of opinion, for which it has set a minimum percentage of 70% agreement between the judges. In the third phase, we selected the affirmative diagnoses/outcomes and nursing interventions based on empirical indicators validated and structured the final version of the instrument. Results: In the first stage, the results are a set of 122 items, items 11 and puerperal identification 111 empirical indicators of human needs. These items have structured the first version of the instrument. In the second phase, five nurses attended to validate the items that composed the first version. The results show the agreement of the judges on all items presented, although they have been suggested for the inclusion and exclusion of some items. In the third phase, the empirical indicators were grouped so as to favor the selection of diagnoses/outcomes and nursing interventions proposed in previous studies, using the International Classification for Nursing Practice. We selected 17 diagnoses/results nursing, diagnostic drafted a statement (totaling 18 affirmative) and 52 selected nursing interventions. The final instrument was structured in three parts: data identification postpartum; assessment of basic human needs, and planning, prescription and evaluation of nursing. Conclusion: Although the proposed objective has been achieved, it is necessary to conduct further studies to operational testing of the instrument, validation of affirmative diagnosis by expert nurses and clinical validation of the instrument. It is expected that this instrument is applied in care practice and teaching. E contributes to improved quality of care, supports the documentation of nursing to give visibility to professional practice in attention to women immediately postpartum.